Effect of periodized strength training on body composition and physical fitness in elderly women - Assumpção, Claudio de Oliveira (2008)
The aim of this study was to analyze the effects of a 12 weeks periodized strength training on body composition and physical fitness in active elderly women. 28 volunteers aged 65.5 ± 3.6 years, with a minimal one year of previous experience in strength training were selected. The participants were randomly divided into 2 groups: G1P (n=16, periodized group) and G2NP (n=12, nonperiodized group). The training was composed by two weekly sessions. Body mass index (BMI), body fat, arm flexion, vertical jump, flexibility and VO2max were measured. The body fat percentage decreased in G1P. There was an increase in arm flexion vertical jump and VO2max in G1P. There were no significant alterations in G2NP. It is concluded that periodization of strength training positively influenced body composition and physical fitness variables, showing that this may be an important tool in strength training prescription.